Ocular Morbidity in Patan Community Based Rehabilitation Center - Shrestha, Sabina; Manoranjan, Aparajita; Shrestha, Sushan Man (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Community based rehabilitation centers work for the betterment of people with disabilities within the communities. This study was conducted to find out ocular morbidity in Patan community based rehabilitation center.Methods: A cross-sectional study was conducted at Patan Community Based Rehabilitation Center, Patan at Lalitpur district of Nepal with sample size of 42, where children and adults of different age groups come on daycare basis. All patients underwent assessment of visual acuity, orthoptic evaluation, anterior segment and posterior segment evaluation and cycloplegic refraction.Results: Age ranged from 7 to 35 years (mean age 14.5 years) with 64.28% of participants within the age group 11-20 years followed by 26.19% within the age group 1-10 years. Male:Female ratio was 1:1.33. Regarding the ethnicity, 71.43% comprised of Tibeto-Burman origin and 28.57% of Indo-Aryan origin.Regarding the general morbidity, 40.48% among the participants had intellectual disability, 16.67% had autism, 14.29% had cerebral palsy, 11.90% had down syndrome, 11.90% had multiple disabilities, 2.38% had physical disability and 2.38% had visual impairment.Regarding the ocular diseases, 26.19% had refractive error only, 19.04% had strabismus only, 9.52% had refractive error and strabismus, 4.76% had cataract, 2.38% optic atrophy and 2.3% had retinitis pigmentosa.Conclusion: Refractive error and strabismus are the commonest ocular morbidities found in Patan community based rehabilitation center.